A espiritualidade através do sentido de vida : um fator de proteção para estudantes do Ensino Médio - Cristino, Ana Caroline Cabral (2024)
Spirituality, through the path of meaning in life, is an important aspect for human development. Therefore, it is necessary to carry out an increasingly consistent dialogue between the area of Applied Study of Religion with the approach of Viktor Frankl's Logotherapy and Existential Analysis in the educational context. The inclusion of spirituality in educational institutions contributes to promoting the psychological well-being of adolescent students, as the spiritual field is part of the understanding of health. The present study initially carried out theoretical discussions through literature reviews in the context of spirituality, meaning in life, education in adolescence and mental health. Then, two empirical studies were carried out. The first, based on a sequential exploratory intervention, analyzed associations between spirituality, meaning of life, depression, anxiety and stress in a sample of 152 students, using a sociodemographic questionnaire and the following instruments (Brazilian versions): Meaning of Life Questionnaire (MLQ), World Health Organization Quality of Life Instrument – Abbreviated Spirituality, Religiosity and Personal Beliefs Module (WHOQOL-SRPB BREF) and Depression, Anxiety and Stress Scale for Adolescents (DASS-21). The second quantitatively evaluated an experiential project to find the meaning of life, comparing results from the MLQ, WHOQOL-SRPB BREF and DASS-21 between an experimental group (n=15) and a control group (n=15). In addition, qualitative analysis of written records of students in the experimental group was carried out using the Iramuteq software. The quantitative results showed: positive association between spirituality and meaning in life through the presence of meaning factor; negative association between spirituality and depression and stress; and negative association between the search for meaning and depression and stress. Furthermore, they also indicated a positive association between the level of spiritual/religious belief and spirituality. The qualitative results showed that the six meetings of the experiential project guided the human movement towards transcendence towards the encounter with the meaning of life, the realization of experiential, attitudinal and creative values of Logotherapy and Existential Analysis and helped to regulate negative emotional states.